Functions of teacher authority in classroom interaction: Investigating contexts for language learning - Munir, Fouzia (Jurnal Cakrawala Pendidikan, 2025)
Classroom interaction is fundamental to any pedagogical practice. Through interaction, teachers accomplish the tasks of teaching and managing classroom activities. Whatever approach a new or experienced teacher takes to teaching, classroom communication mediates between teaching and learning. The teacher–student relationship is inherently asymmetrical, where the teacher has the power to establish different contexts for language use and learning in a classroom and to control student behaviour. The aim of the study is to investigate the typical discursive structures of classroom interaction to determine the different contexts for language learning. Qualitative data were collected from five schools in the Eastern Cape, South Africa. The data were analysed using theoretical and analytical models from conversation and discourse analysis. The findings revealed that teachers use their authority and power to set up contexts where learners participate in different forms of interaction, which have different implications for language learning. In some contexts, the teacher controls interaction strictly; in others, the students have more power over their interaction. Teachers must be cognisant of their choices to make informed pedagogical decisions in their language classrooms.